A Learning Curve‐Based Assembly Game. (12th November 2019) - Robbins, Thomas R.
ABSTRACT: This article describes a game used in an MBA‐level operations management course to help students understand the concept of the learning curve. Student teams participate in an interactive, hands‐on Lego assembly exercise, measuring their times through repeated trials after which they calculate their team's learning curve rate. The exercise is oriented to illustrate the mechanisms by which learning occurs both individually and organizationally. After students complete their work in groups, the data is aggregated across the class and analyzed to further illustrate key principles of the learning curve. A modified version of the game based on cup‐stacking has been developed for online students.